The Psychological Impact of Covid-19 on Nurses at the Central Hospital in Vientiane, Lao PDR: https://doi.org/10.69692/SUJMRD1004111 - Syhalath, Eungkham; PHANPASEUTH , Souksavanh; SYSOULATH , Anousone; SIKHOTCHOUNLAMANY , Souphavalath (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research was a descriptive research that aimed to study the psychological impact of the covid-19 outbreak on nurses at the central hospital in Vientiane, Lao PDR. The sample group was 328 of nurses and analyzed the data by using the SPSS program. The results of the research found that the impact of the epidemic of covid-19 was mostly psychological with a moderate anxiety in neuwtral level of 59.1%. The psychological impact with stress was at a high level of 95.1% and the psychological impact with depression was at the highest level of 98.4%.